Prenatal care utilization in Zimbabwe: Examining the role of community-level factors - Marshall Makate; Clifton Makate (Springer, 2019)
This paper assesses the importance of community-level factors on prenatal care utilization in Zimbabwe. The analysis is performed using data from the two most recent rounds of the nationally representative Demographic and Health Survey for Zimbabwe conducted in 2005/06 and 2010/11 linked with other community-level data. We use logistic, generalized linear regressions as well as multilevel mixed models to examine the factors associated with the frequency, timing and quality of prenatal care. Our results suggest that contraceptive prevalence, religious composition, density of nurses, health expenditures per capita and availability of government hospitals in communities are important predictors of prenatal care use in Zimbabwe. These findings have important implications for public health policy in Zimbabwe - a country with unfavorable maternal and child health outcomes.